Adiposity and weight gain in Mangalarga Marchador horses subjected to hypercaloric diet - Rodrigo M. Ribeiro; Debora S.F. Ribeiro; Cahue F.R. Paz; Alexandre A.O. Gobesso; Rafael R. Faleiros (Pesquisa Veterinária Brasileira)
ABSTRACT: In recent years, several researchers have been studying obesity in national horse breeds; however, no studies demonstrating the dynamic of body and regional fat accumulation (adiposity) Mangalarga Marchador horses subjected to hypercaloric diets have been found. This study aimed to characterize the deposition of body and regional fat in horses with diet-induced weight gain. A total of nine Mangalarga Marchador adult horses with initial body condition score (BCS) of 2.9 ±1/9 (mean ±SD) were subjected to a hypercaloric, grain-rich diet for five months. Body weight and the following morphometric regional adiposity variables were analyzed: BCS, cresty neck scores (CNS), neck circumferences (NC) at 25, 50 and 75% of its length, and accumulation of subcutaneous adipose tissue at the base of the tail using ultrasonography (BTU). These data were collected at baseline and fortnightly after beginning the diet-induced weight gain until the end of the experiment. The effect of time on the variables was verified by analysis of variance (ANOVA) in randomized blocks or the Friedman’s test, and the means were compared by the Tukey’s test (p≤0.05). Exposure to hypercaloric diet promoted a mean weight gain of 27.45% (p<0.001). Significant values were observed for NC at 25 and 75% during the first 45 days of the experiment, and for NC at 50% during the first 30 days. BTU presented significant changes after 60 days, with an increase of 268% compared with the baseline value. These findings demonstrate the weight gain and the dynamic and magnitude of regional adiposity in Mangalarga Marchador horses subjected to hypercaloric diet.